Fator de cubicação para madeira empilhada de Eucalyptus grandis W. Hill ex Maiden, com toretes de dois comprimentos, e sua variação com o tempo de exposição ao ambiente - Barros, Marcos Vinicios (2006)
The express wood volume in meter estere (mst) sometimes need to be converted into cubical meters (m3). This is possible estimating a cubication factor (Fc). With the objective to determine the Fc for Eucalyptus grandis and its variation in pieces of wood of different lengths of 1 and 2,3m of length in reason of the time of exposure to the enviroment, in the summer and the winter. Six stacks of wood pieces 3X2X1m (width, height and depth) dimensions had been prepared and six stacks of wood pieces in the dimensions 3X2X2,3m, installed in the summer and winter. The Fc was obtained by volume reason, with CV of 4,2 to 9,5% and by angular counting with CV of 10,9 to 17%. Thus, continued analysis with Fc s average obtained by reason of volumes because they had presented minor variation. The analysis statistics for factorial experiment(2X2X6), indicated significant difference (α<5%) in the variations of principal effect, that is, in the climatic station (F=18,72) , in the time of exposure (F=6,51) and in the length of the different pieces of wood (F=35,18) .The analysis of the correlation of Pearson indicated that the Fc was also influenced by the cracks on top, the humidity of the wood and the atmospheric variable, in the two observed seasons. Evidenced variation of the Fc of the stacks in exposition, equation with use of Stepewise procedure was shaped for the independent variable: T, T2, T3, T4, T5, 1/T, 1/T2, 1/T3, 1/T4, 1/T5, log(T), log(1/T), log(lnT), 1/lnT, 1/log(T), the equation with the best adjustment was decurrent of short pieces of wood of winter for an initial period until 90 days after installation. Adjusted the equation Fc=0,70385+0,00000961(T2), with values of F and R2 equal 17,22 (Pr>F=0,2%) e 0,63, respectively. However the averages of the value of the Fc obtained by observation and the estimator are the same (0,74) and the model was more accurate, then was opted to using the average gathered by each month. The conversion chart of the volume estere in cubical volume was completed since specific average values of the Fc for the climatic stations summer and winter and for the two lengths of pieces of wood, obtained by reason of volumes. The average values of the Fc s had indicated a stabilization after ninety days of the installation of the stacks, with this subdivided the time of exposure in two periods: one from zero to ninety days and another one from ninety to one hundred and eighty days, these compared with the total of the observations (180 days), the average values of these observations had not presented significant difference by the Tukey test (α<5%). However, pieces of wood of Eucalyptus grandis had presented dimensional variation when displayed in inclement weather for a period of one hundred and eighty days (six months) making the cubication factor Fc to vary in elapsing of the period of exposition.